Isolation and functional characterization of the high-affinity phosphate transporter, PHT1, gene promoter of oil palm (Elaeis guineensis Jacq.) - Ahmadi, Farzaneh (2017)
Phosphorus is one of the least available elements for plant growth especially in tropical soils. The high-affinity Pi transporters are assumed to be the main system responsible for Pi uptake by plant roots. The objectives of the study were to isolate the promoter of the high-affinity phosphate transporter gene from oil palm (EgPHT1) and to perform functional characterization using transgenic Arabidopsis and transient expression assay in oil palm tissues. The third objective was to study the effects of some exogenous signals and abiotic factors on the EgPHT1 promoter activity. Analysis of the isolated full-length EgPHT1 promoter region (1467 bp) using PLACE and PlantCARE databases revealed the presence of a number of putative cis-regulatory elements associated with response to Pi and various environmental and biotic-stress signals. Under Pi deprivation, excessive quartenary roots formation was observed and the GUS activity was induced to 5.5-fold higher compared to under Pi-sufficient condition in the transiently transformed oil palm roots but no activity was observed in the leaves. In transgenic Arabidopsis, 29-fold greater induction of GUS expression was observed in the Pi-starved roots with no activity in other tissues. Increasing the Pi concentration from 0 to 1250 μM resulted in reduction of the GUS activity from 9109 to 315.3 pmol/min/mg protein in the transgenic plants. As the duration of Pi starvation increased from 1 to 6 days, the GUS activity increased from 660 to 9091 pmol/min/mg protein. Increasing exogenous sucrose concentration from 0.1% to 3% elevated the GUS expression from 296 to 9151.3 pmol/min/mg protein under Pi deprivation. Glucose and fructose as metabolizable sugars could induce the promoter activity, but at low level. Pi deficient inducibilty of the promoter was maintained even under high salinity up to 100 mM. Application of IAA led to strong GUS expression, but BAP suppressed the expression under Pi deprivation. Finally, progressive 5ʹ-deletion analyses of the EgPHT1 promoter demonstrated that the region from - 690to -1 bp as the minimal promoter is sufficient to drive root- and Pi deprivation-specific expression in transgenic Arabidopsis. Deletion of the promoter region containing the P1BS element significantly reduced the promoter activity in the roots. The results also suggest the probable influenced of other positive/enhancer motifs such as W-box, G-box and E-box for maximal promoter activity. While the root-specific motifs ROOTMOTIFTAPOX1 and RAV1AAT BOX are critical for its root-specific activity.This is the first report on the high-affinity Pi transporter gene promoter of oil palm whose activity is induced exclusively in the root under low Pi. It contains the conserved elements for driving expression in both monocots and dicots and would be a potentially valuable candidate as a genetic engineering tool.